IMPLEMENTASI MANAJEMEN KURIKULUM SEBAGAI UPAYA PENINGKATAN KUALITAS PENDIDIKAN DI SD NEGERI 173423 LUMBAN NAUNGKUP - Saragih, Meysi Grace; Simanullang, Marlenni; Simamora, Reli Rita; Hutasoit, Rolambok; Situmorang, Friska Andriani; Simanullang, Pardomuan (JURNAL CURERE, 2023)
Effectiveness and implementation in curriculum development is very dependent on the competence of teachers and the facilities available in schools. It is considered capable of articulating the topics contained in the curriculum. In addition, the success of curriculum development also depends on the management of each teacher. Each of the existing components must be appropriate and well realized. With the suitability and accuracy of each component in the curriculum, it is hoped that the goals and objectives of education will be achieved optimally. Curriculum management is very important, because without management education will not run well. A curriculum that is developed will be meaningless if it is not implemented, in the sense that it is actually used in schools. The success of curriculum management is primarily determined by the aspects of planning and implementing strategies. Curriculum implementation as an integral part of curriculum development requires concepts, principles and procedures as well as management approaches. This study emphasizes the policy of the school leadership at SD Negeri 173423 Lumban Naungkup in implementing curriculum management. The curriculum used at SD Negeri 173423 Lumban Naungkup for grades I to VI uses the 2013 curriculum. Curriculum planning at SD Negeri 173423 Lumban Naungkup uses lesson plans and syllabus as a reference for teachers to teach in class.Keywords: Implementation, Curriculum, Management;